penggunaan filler abu sekam padi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
Dense graded emulsion mix is a cold mix that consists of dense graded aggregates and bitumen emulsion. To increase a density and reduces voids in the mix, a certain filler content is used. Mineral fillers are a fine materials in which more than 70 % of weight passing a sieve No.200